Evaluating Biological Risks in Biomedical Laboratories of Primary Health Care - Vourtsis, Dionysios; Papageorgiou, Efstathia; Kriebardis, Anastasios; Willigen, Gijsbert van; Kotrokois, Kostas; Karkalousos, Petros (European Scientific Journal, ESJ, 2025)
Biomedical laboratories in primary health care centers play a critical role in disease detection, diagnosis, and management. However, the handling of diagnostic samples presents significant biological risks, particularly when biosafety measures are insufficient. This study focuses on analyzing the biological risks in 35 BSL-2 biomedical laboratories within health facilities in Athens, Greece, by examining compliance with biosafety regulations, personnel safety awareness, and biorisk management practices. A cross-sectional survey was conducted combining a customized checklist and a structured health and safety questionnaire, both developed based on the existing literature, including the international biosafety guidelines (BMBL 6th ed., WHO Biosafety Program Management, 2020). On-site evaluations were performed by a certified biorisk management advisor, and 158 laboratory professionals anonymously completed questionnaires on biosafety practices. The collected data were analyzed qualitatively, and where possible, quantitatively, by using SPSS software and p-values from the McNemar test. The results revealed widespread deficiencies in biosafety culture and risk management. Key gaps were identified in all layers of engineering controls, administrative controls, personal protective equipment (PPE), and emergency preparedness. Many laboratories failed to meet international biosafety standards set by organizations such as the WHO, CDC, and ECDC, as well as Greek legislation, highlighting the need for urgent improvements. To address these issues and mitigate the observed gaps, the implementation of comprehensive Biorisk Management Systems, enhanced biosafety training, and stricter enforcement of national and European biosafety regulations is strongly recommended. These measures are essential to protect laboratory personnel, the surrounding community, and the environment from lab-acquired infections and other biological threats.